Early detection of risk of autism spectrum disorder based on recurrence quantification analysis of electroencephalographic signals - Heunis, Tosca-Marie (Stellenbosch : Stellenbosch University, 2016)
Thesis (PhD)--Stellenbosch University, 2016.